Economic Analysis of Coffee Subsector in Nepal - Paudel, Indra Hari (Journal of Agriculture and Environment, 2023)
Coffee being one of the emerging crops with high potential to export to earn foreign currency, has been given due importance by the Government of Nepal. Among different agricultural goods produced in and exported from Nepal, the competitiveness of coffee has quickly increased in recent years, thus contributing to the improvement of rural livelihoods. This study was based on review of literature and analysis of secondary data/information. Statistical tools such as correlation analysis was also used to analyze data. According to the official records coffee production area has expanded from around 135.7 ha in fiscal year 1994/95 to 3052 ha in 2020/21 and the production has increased from 12.95 Mt. of dry cherry to 315 Mt. of green beans during the same period. Nepal’s coffee subsector is characterized by low productivity, low production and poor quality. Inter alia, it was mainly due to incidence of insect pests, production done by smallholder farmers in a widely scattered area creating problems in quality control and collection leading to higher cost. The good price, high demand and overwhelmingly organic system of production are the encouraging factors but the formidable challenge remains on fighting with white stem borer and providing incentives for small holder farmers throughout the relatively long gestation period of coffee crop. Apart from low production level, organic certification and quarantine requirements pose serious challenges to export. Coffee produced in Nepal is Organic & Fair-trade and is readily accepted as a Specialty Coffee in specific international markets.